Stock Assessment and Sustainable Potential of Skipjack Tuna (Katsuwonus pelamis) in Sibolga Waters for Optimized Fishing Practices - Limbong, Irwan; Brown, Arthur; Isnaniah, Isnaniah; Kholis, Muhammad Natsir (Journal of Coastal and Ocean Sciences, 2025)
The uncontrolled fishing of skipjack tuna (Katsuwonus pelamis) without recruitment efforts has led to stock degradation and unstable abundance due to excessive pressure. This study aims to estimate the sustainable potential of skipjack tuna by calculating Catch per Unit Effort (CPUE), assessing Maximum Sustainable Yield (MSY), and determining Total Allowable Catch (TAC). The research was conducted at PPN Sibolga and utilized survey-based data collection and surplus production analysis using the Schaefer model. The findings indicate that standardized CPUE in 2018 was 0.639 tons/trip, increased to 0.764 tons/trip in 2019, dropped to 0.527 tons/trip in 2020 and 0.506 tons/trip in 2021, and returned to 0.639 tons/trip in 2022. Purse seines were identified as the primary fishing gear. The Schaefer model estimated CMSY at 8,699.7 tons, classifying the fishery as fully exploited. FMSY was calculated at 5,447 trips, with annual efforts consistently exceeding this threshold, indicating overfishing. The TAC was set at 6,959.7 tons. Management strategies should regulate fishing efforts, enforce gear specifications, and implement science-based fisheries policies to prevent further degradation. Aligning fishing activities with sustainable thresholds will support skipjack tuna stocks' recovery and long-term productivity. These findings underline the importance of adaptive management and collaboration to sustain marine ecosystems and protect livelihoods